2013
DOI: 10.1007/s11033-013-2800-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the bovine DKK2 and their associations with body measurement traits and meat quality traits in Qinchuan cattle

Abstract: The objective of this research were to detect bovine Dickkopf 2 (DKK2) gene polymorphism and analyze their associations with body measurement traits (BMT) and meat quality traits (MQT) of animals. Blood samples were taken from a total of 541 Qinchuan cattle aged from 18 to 24 months. Polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) was employed to find out DKK2 single-polymorphism nucleotide (SNPs) and to explore their possible association with BMT and MQT. Sequence analysis of DKK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Currently, research on DKK2 primarily focuses on tumors, with several papers reporting abnormal expression of DKK2 in tumor tissues [ 60 62 ]. Furthermore, studies have indicated that the SNP (C29T) in exon 1 of the DKK2 is associated with intramuscular fat content in Qinchuan cattle [ 63 ]. In experiments using c3h/10t1/2 mesenchymal stem cells of mice, researchers have verified that the DKK2 can inhibit lipogenesis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, research on DKK2 primarily focuses on tumors, with several papers reporting abnormal expression of DKK2 in tumor tissues [ 60 62 ]. Furthermore, studies have indicated that the SNP (C29T) in exon 1 of the DKK2 is associated with intramuscular fat content in Qinchuan cattle [ 63 ]. In experiments using c3h/10t1/2 mesenchymal stem cells of mice, researchers have verified that the DKK2 can inhibit lipogenesis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARGC1A and FOXO1 also induce SESN2 and TRIM63 expression, both of which are important players in controlling lipid metabolism by enhancing mitochondrial biogenesis and shuttling adenosine triphosphate to myofibrils in mice, respectively (Seo, Seo, Ki, & Shin, ; Willis et al., ). DKK2 , another target gene for PPARGC1A and FOXO1 , is associated with intramuscular fat content and backfat thickness in cattle (Zhan, Gao, Huangfu, Fu, & Zan, ). Therefore, the data from the IPA analysis indicating that the adipogenic effects of Amaize as indicated by higher backfat in the Amaize group was likely driven by the upregulation of lipid deposition‐related genes in skeletal muscle, including PPARGC1A , ABRA , FOXO1 , FNIP2 , APOC3 , SESN2 , TRIM63 , and DKK2 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study with experimental rat population, the DKK2 gene was related with postnatal development and growth (Bodine et al, 2004). Zhan et al (2015), also associated the expression of this gene with skeletal growth traits as well as meat quality traits in Qinchuan cattle.…”
Section: Additive Direct Genetic Effectmentioning
confidence: 99%